Heat Unit Requirement for Growth and Development of Pearl Millet - Bishnoi, O P; Rao, V Umamaheshwara; Singh, Diwan (Annals of Arid Zone, 2016)
The experiment on the heat unit requirements of four pearl millet varieties had three dates of sowing. The heat unit requirement for emergence of leaves did not differ within varieties upto 4 or 5 leaf stage but the difference surfaced later on, towards emergence of the last leaf. The heat unit requirement for appearance of nodes was almost similar and in variety BJ 104 it was maximum (1152.5 dayÂ°C). The variety HC-4 accumulated maximum heat, units. With consecutive delay in sowing from 18 July to the following two dates. the heat unit requirement for year emergence, seed setting and maturity increased.